2001
DOI: 10.1007/s004260000043
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning enhances perceptual judgment: a case for action-perception transfer

Abstract: Transfer from perception to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 29 publications
12
103
0
Order By: Relevance
“…An important aspect appears to be that perceptual or "observational learning" has to be explicit, i.e., conscious (Willingham, 1999;Kelly and Burton, 2001). More recent experiments have provided evidence that transfer between perception and action is bidirectional, as transfer both from action to perception and from perception to action was found (Hecht et al, 2001). These findings were taken to support the assumption of a "common coding" of perceptual and motor events (Prinz, 1997).…”
Section: Serial Prediction Activates Ventrolateral Premotor Cortex Anmentioning
confidence: 75%
“…An important aspect appears to be that perceptual or "observational learning" has to be explicit, i.e., conscious (Willingham, 1999;Kelly and Burton, 2001). More recent experiments have provided evidence that transfer between perception and action is bidirectional, as transfer both from action to perception and from perception to action was found (Hecht et al, 2001). These findings were taken to support the assumption of a "common coding" of perceptual and motor events (Prinz, 1997).…”
Section: Serial Prediction Activates Ventrolateral Premotor Cortex Anmentioning
confidence: 75%
“…Casile and Giese showed that the discrimination of point-light displays of gait patterns was selectively enhanced after purely motor training of a corresponding, novel phase relationship of the upper limbs, thus providing further evidence for direct matching. However, the authors did not study whether the kinaesthetic information available during motor training might have been sufficient for the transfer effect; thus the same caveat applies to this study as to the original work by Hecht et al (2001).…”
Section: Inter-limb Coordinationmentioning
confidence: 89%
“…A timing task was also used to explore actionperception transfer (APT; Hecht, Vogt, & Prinz, 2001). Whereas the study of observational learning, or transfer from perception to action (PAT), has a long history, virtually no research was available to indicate if motor practice would transfer to perceptual skills.…”
Section: Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha was set at p < 0.05, and eta squared (ƞ 2 ) expressed the size of the effect. 20 facilitate positive transfer from imitation to subsequent motor performance (Hecht, et al, 2001). In the 21 current study, we further examined whether higher-order processes developed using reduced-22 frequency feedback procedures in motor training transfer to imitation.…”
Section: Motor Training Task 14mentioning
confidence: 97%